2015
DOI: 10.1080/02589001.2015.1024007
|View full text |Cite
|
Sign up to set email alerts
|

The promises and realities of Ghana's decentralization: a case study from the Wenchi district of Ghana

Abstract: This article explores the functioning of the decentralized structures in Wenchi district of Ghana with the view of generating deeper insights into the interplay between decentralization outcomes and prevailing social, economic, and cultural realties of the people. Data were collected from both secondary and primary sources. The main findings of the study indicate that sub-district structures do not provide an effective platform for citizen participation. Elections were found to primarily be an instrument for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
6
1
Order By: Relevance
“…The kinds of engagement and consultation required to reach the desired consensus would be, however, impossible if the needed resources were not available to animate communities; hence the need for deliberate policy action to ensure that the requisite resources were made available for the planning process in the district. The findings established provide a different understanding from the conclusions drawn in a previous study by Adams and Taabazuing (2015). While these authors concluded that there was general apathy towards opportunities (meetings) for participation in decision making, this study found that there was a lack of opportunity for communities to participate effectively in shaping their development.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…The kinds of engagement and consultation required to reach the desired consensus would be, however, impossible if the needed resources were not available to animate communities; hence the need for deliberate policy action to ensure that the requisite resources were made available for the planning process in the district. The findings established provide a different understanding from the conclusions drawn in a previous study by Adams and Taabazuing (2015). While these authors concluded that there was general apathy towards opportunities (meetings) for participation in decision making, this study found that there was a lack of opportunity for communities to participate effectively in shaping their development.…”
Section: Discussioncontrasting
confidence: 94%
“…It is important to note that previous studies on the decentralisation in Ghana have looked at the efficiency of the local government structure in Ghana and how it promotes effective participation in decision making (see e.g. Adams and Taabazuing, 2015). The study revealed that there was general apathy by the citizenry towards participating in the decision making process, citing the inability of elected representatives to influence implementation of their decisions as a major reason.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Von Braun and Grote (2002) failed to find clear evidence of decentralization enhancing participation in China, India, Ghana, and Egypt; they observed that citizen participation is not guaranteed unless fiscal decentralization is preceded by political and administrative decentralization in these countries. Adams and Taabazuing (2015) also point to limited citizens' participation in Ghana's decentralization. Similarly, Bulut and Abdow (2018) reported low citizen participation under decentralization in Kenya.…”
Section: Decentralization and Participation: A Brief Overview Of Theo...mentioning
confidence: 97%
“…It would be difficult for the district officials to truly know the problems of the poor without broadly involving them in any of the planning and decision-making structures (Adams and Taabazuing 2015). For a development plan to be responsive to the needs of the poor, the district planners must plan with the poor, and not plan for them.…”
Section: How Pro-poor Are the Participation Structures And Processes?mentioning
confidence: 99%
“…Many studies have examined the determinants and impact of decentralization in terms of economic growth, income inequality, poverty, and social capital (Davoodi and Zou, 1998; De Mello, 2011; Sepúlveda and Martínez-Vázquez, 2011; Tselios et al, 2012), but not much has been done on the issue of the election v. appointment of the political head of the assembly. Though a number of studies have examined the performance of Ghana’s decentralization and district assembly structures (Adams, 2016; Adams and Taabazuing, 2015; Crawford, 2004; IFPRI, 2009; Nyendu, 2012), there is a dearth of scholarship on the best institutional arrangement for choosing MMDCEs. Obviously, if the essence of decentralization is to improve citizens’ welfare, then the need to determine their perception of the best way of choosing the Chief Executive cannot be overemphasized.…”
Section: Introductionmentioning
confidence: 99%